2023
DOI: 10.1002/csr.2460
|View full text |Cite
|
Sign up to set email alerts
|

Walking the tightrope: Circular economy breadth and firm economic performance

Abstract: The circular economy (CE) can bring benefits but also pitfalls to the production processes, affecting a firm's economic performance. Using data from European SMEs, we empirically investigate, from the perspective of self-determination theory, the extent to which the breadth of CE activities, that is, the number of CE activities undertaken by a firm, affects a firm's economic performance. Our study theorizes and shows that there is an inverted U-shaped effect brought about by the number of CE activities on econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…[ 17 ] asserted that “ the circular economy (CE) can bring not only benefits but also pitfalls to production processes, affecting a firm's economic performance ”.…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…[ 17 ] asserted that “ the circular economy (CE) can bring not only benefits but also pitfalls to production processes, affecting a firm's economic performance ”.…”
Section: Literature Reviewmentioning
confidence: 94%
“…In contrast, Gonçalves and colleagues [ 2 ] found that the link between CE and financial performance is weak and incipient. Similarly, D'Angelo and colleagues [ 17 ] reported the existence of an inverted U-shaped effect brought about by the number of CE strategies on economic performance. One of the reasons for this is that when a company focuses on multiple CE strategies, it could be perceived negatively by the market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Initial investment: the adoption of practices and technologies based on the EC can mean different significant investments from public or private companies, which can mean a great barrier especially for those that are small and medium-sized (206).…”
Section: Challenges and Barriersmentioning
confidence: 99%
“…ORP involves measuring the efficiency and effectiveness of firms' operations, such as productivity, quality, and innovation (Chiappetta Jabbour et al, 2020). In addition to these variables, other firm performance variables include financial performance, such as total annual sales per employee, market share, brand reputation, and time-to-market (De Lima & Seuring, 2023;Sarfraz et al, 2019;D'Angelo et al, 2023;Fernando et al, 2023;Mazzucchelli et al, 2022;Rodríguez-González et al, 2022;Blasi et al, 2021;Bartolacci et al, 2018). These variables are used to measure the competitiveness and market position of firms.…”
Section: Ce Practices and Firm Performancementioning
confidence: 99%